2022
DOI: 10.1186/s12913-022-08255-0
|View full text |Cite
|
Sign up to set email alerts
|

Initial presentation for acute low back pain: is early physical therapy associated with healthcare utilization and spending? A retrospective review of a National Database

Abstract: Background Early initiation of physical therapy (PT) has been associated with lower healthcare costs and utilization; however, these studies have been limited to single institutions or healthcare systems. Our goal was to assess healthcare utilization and spending among patients who present for the first time with low back pain (LBP), according to whether they received early physical therapy (PT), using a large, nationwide sample; and geographic variation in rates of early PT and 30-day LBP-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The VHA CDW system likely contains discrepancies common to large data warehouses, such as miscoding, mislabeling, and discrepancies in updating data. 48 , 49 , 50 Despite this, previous work has shown much reason to be confident in the accuracy of VHA CDW data. 51 , 52 The “TCC only” group of patients contained primarily telephone visits that did not represent the full breadth of chiropractic telehealth.…”
Section: Discussionmentioning
confidence: 99%
“…The VHA CDW system likely contains discrepancies common to large data warehouses, such as miscoding, mislabeling, and discrepancies in updating data. 48 , 49 , 50 Despite this, previous work has shown much reason to be confident in the accuracy of VHA CDW data. 51 , 52 The “TCC only” group of patients contained primarily telephone visits that did not represent the full breadth of chiropractic telehealth.…”
Section: Discussionmentioning
confidence: 99%
“…12 Also, a recent evaluation of almost one million outpatient visits for acute LBP found that the minority (11%) of patients referred to prompt (less than 15 days after presentation) PT incurred significantly lower health care costs. 13 Similarly, a large study of early PT for acute LBP found significant reductions in subsequent use of lumbosacral injections, lumbar surgery, and frequent physician office visits for LBP. 14 A clinic created in the US military to promptly evaluate acute LBP (with opportunity for medication receipt) by PTs found improved outcomes, including less medication and imaging.…”
Section: Introductionmentioning
confidence: 98%
“…A study of US Army soldiers found early treatments for LBP improved military readiness outcomes 12 . Also, a recent evaluation of almost one million outpatient visits for acute LBP found that the minority (11%) of patients referred to prompt (less than 15 days after presentation) PT incurred significantly lower health care costs 13 . Similarly, a large study of early PT for acute LBP found significant reductions in subsequent use of lumbosacral injections, lumbar surgery, and frequent physician office visits for LBP 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Among persons with LBP, rates of opioid prescribing are about double rates of nonpharmacologic care. [8][9][10][11][12][13][14] Considerable disparities exist in chronic pain prevalence and management. Prevalence is higher among persons with less income or education, and in rural communities.…”
Section: Introductionmentioning
confidence: 99%